DEVELOPING TEACHER’S PROFESSIONAL ACTIVITIES USING INFORMATION TECHNOLOGIES (Web of Teachers: Inderscience Research, 2024)
This article is devoted to a detailed disclosure of the pedagogical conditions, didactic possibilities, and methods for developing methodological foundations for the use of innovative approaches in the development of teachers' professional activities based on information technologies.